2016
DOI: 10.1113/jp270878
|View full text |Cite
|
Sign up to set email alerts
|

Age protects from harmful effects produced by chronic intermittent hypoxia

Abstract: Obstructive sleep apnoea (OSA) affects an estimated 3–7% of the adult population, the frequency doubling at ages >60–65 years. As it evolves, OSA becomes frequently associated with cardiovascular, metabolic and neuropsychiatric pathologies defining OSA syndrome (OSAS). Exposing experimental animals to chronic intermittent hypoxia (CIH) can be used as a model of the recurrent hypoxic and O2 desaturation patterns observed in OSA patients. CIH is an important OSA event triggering associated pathologies; CIH induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
1
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(72 citation statements)
references
References 77 publications
7
55
1
9
Order By: Relevance
“…; Quintero et al . ). In line with these results we found here that the basal level of CSN activity was unchanged with age, but when hypoxia was applied the response in the old animals was markedly decreased for all hypoxic levels tested (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…; Quintero et al . ). In line with these results we found here that the basal level of CSN activity was unchanged with age, but when hypoxia was applied the response in the old animals was markedly decreased for all hypoxic levels tested (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…However, at least in chronic intermittent hypoxia age exerts a neuroprotective effect against its harmful effects, since in aged rats chronic intermittent hypoxia does not alter carotid body responses, catecholamine‐related parameters or redox status, and does not cause hypertension (Quintero et al . ). The lack of harmful effects observed in chronic intermittent hypoxia in ageing (Quintero et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In this context, Quintero et al have also shown that age protects from the harmful effects of CIH (13). Since OSA is clinically less conspicuous in aged patients, they compared CIH effects in young (3-4 months) and aged (22-24 months) rats.…”
Section: Spontaneous Tumorigenesis Induced By Intermittent Hypoxia Inmentioning
confidence: 99%